Associations Between Plasma Immunomodulatory and Inflammatory Mediators With VACS Index Scores Among Older HIV-Infected Adults on Antiretroviral Therapy - Premeaux, Thomas A.; Javandel, Shireen; Hosaka, Kalei R. J.; Greene, Meredith; Therrien, Nicholas; Allen, Isabel E.; Corley, Michael J.; Valcour, Victor G.; Ndhlovu, Lishomwa C. (Frontiers in Immunology, 2020)
The prevalence of age-related comorbidities is increased in people living with HIV, even in those well-controlled on combination antiretroviral therapy (ART). Persistent immune activation and inflammation may play pivotal roles in the pathogenesis; however, the burden of morbidities in the older HIV infected population may be exacerbated and driven by distinct mechanisms. In a cross sectional study of 45 HIV-infected participants 60 years or older, we examined the relationships between 14 immunomodulatory and inflammatory factors and the Veterans Aging Cohort Study (VACS) Index, a metric of multimorbidity and mortality comprised of clinical components (age, CD4 count, hemoglobin, Fibrosis-4 [FIB-4]), and estimated glomerular filtration rate [eGFR], by linear regression analysis. All participants were virally suppressed (<50 HIV RNA copies/mL), on ART, and primarily Caucasian (86.7%) and male (91.1%). Plasma levels of monocyte/macrophage-associated (neopterin, IP-10, sCD163, sCD14, and MCP-1) and glycan-binding immunomodulatory factors (galectin (Gal)-1, Gal-3, and Gal-9) were assessed, as well as inflammatory biomarkers previously linked to the VACS Index (i.e. CRP, cystatin C, TNF-α, TNFRI, IL-6, and D-dimer) for comparison. In regression analysis, higher VACS index scores were associated with higher levels of neopterin, cystatin C, TNFRI, and Gal-9 (all p<0.05), potentially driven by correlations found with individual VACS components, including age, CD4 count, FIB-4, and eGFR. Gal-9, cystatin C, and TNFRI directly correlated with the extent of multimorbidity. Multiple correlations among markers were observed, suggesting an interplay of overlapping, but distinct, pathways. Collectively, in addition to cystatin C and TNFRI, both galectin-9 and neopterin, independently emerged as novel fluid markers of the VACS Index score multimorbidity which has been linked mortality risk and may guide in understanding pathogenic mechanisms of age-related disorders in older HIV-infected individuals on suppressive ART.